2010
DOI: 10.1590/s1679-87592010000300004
|View full text |Cite
|
Sign up to set email alerts
|

Chemical defenses of the tropical marine seaweed Canistrocarpus cervicornis against herbivory by sea urchin

Abstract: A B S T R A C TThis paper reports on the defensive chemical properties of the marine tropical brown seaweed Canistrocarpus cervicornis against herbivory. A natural concentration of dichloromethane crude extract (DCE) obtained from this seaweed significantly inhibited feeding by the sea urchin Lytechinus variegatus. The major metabolite isolated from this active DCE extract was identified as the (4R,7R,14S)-4α,7α-diacetoxy-14-hydroxydolast-1(15),8-diene that strongly inhibited feeding by the same sea urchin. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 32 publications
0
16
0
3
Order By: Relevance
“…In the same study, A. fragilissima was observed in tide pools of protected reef areas, which may possibly explain the great number of individuals associated with this phytal. However, D. cervicornis was recorded on irregular patches in tide pools and relatively protected reef areas, but this alga produces diterpenes that repel many invertebrate organisms (BIANCO et al 2010), which may explain its low number of associated Polyplacophora.…”
Section: Discussionmentioning
confidence: 99%
“…In the same study, A. fragilissima was observed in tide pools of protected reef areas, which may possibly explain the great number of individuals associated with this phytal. However, D. cervicornis was recorded on irregular patches in tide pools and relatively protected reef areas, but this alga produces diterpenes that repel many invertebrate organisms (BIANCO et al 2010), which may explain its low number of associated Polyplacophora.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed that some of these chemicals may act as chemical defences able to deter a broad range of natural enemies, including competitors [2], epiphytes [3], herbivores [4], and others [5]. Among the red seaweeds, the genus Laurencia produces the richest variety of secondary metabolites, generating more than 500 previously described compounds [1], [6].…”
Section: Introductionmentioning
confidence: 99%
“…A escolha pode ser induzida por elementos químicos (tóxicas e/ou impalatáveis) presentes no alimento (McConnell et al, 1982;Paul & Fenical, 1986;Hay & Fenical, 1988;Hay et al, 1994;Blunt et al, 2009;Bianco et al, 2010;Machado et al, 2010) e também por diferentes cores e formas das diferentes espécies de presa (Littler et al, 1983;Manly et al, 2006). A relação com outras espécies também é um fator que pode influenciar a seleção alimentar por parte de um animal (Souza et al, 2008).…”
Section: Introductionunclassified
“…As algas marinhas produzem compostos secundários como terpenos, polifenóis, acetogeninas, entre outros (McConnel et al, 1982;Blunt et al, 2009;Bianco et al, 2010). Em ouriços do mar esses compostos interferem na reprodução (Paul & Fenical, 1986).…”
Section: Introductionunclassified
See 1 more Smart Citation